Between mandate and motivation: bureaucratic behavior in global climate governance - Well, M.; Saerbeck, B.; Jörgens, H.; Kolleck, N. (Global Governance, 2020)
International Public Administrations (IPAs) play a significant role for the success of multilateral negotiations. As the bureaucratic bodies of international organizations, they are deeply involved in international negotiations, but receive little credit for their outcomes. By studying the administrative styles of the Secretariat of the United Nations Framework Convention on Climate Change (UNFCCC), we arrive at an understanding of how this IPA aims at contributing to the outcome of multilateral climate change negotiations. Administrative styles can be conceived of, ideal-typically, as being entrepreneurial or servant-like, with the former entailing advocacy in policy-making and the latter characterized by the strict adherence to formal and legal arrangements. We observe that, despite a prohibitively strict mandate as a technocratic facilitator, the UNFCCC Secretariat adopts an entrepreneurial style at the policy initiation stage and a cautiously entrepreneurial style during the phase of policy formulation. It has acquired a distinctive actor quality in the climate regime, motivated by a strong commitment to furthering meaningful cooperation and driving the UNFCCC process towards ambitious climate policies.